In memoriam profesor Ioan Drăgan (22.08.1931-05.12.2024) - Sorin Mitulescu (Sociologie Românească)
Professor Ioan Drăgan was the head of the sociology department at the University of Bucharest (1974-1978) and director of the Center for Sociological Research (1974-1990) and then of the Institute of Sociology of the Romanian Academy (1990-1997). He has taught courses in general sociology and sociology of public opinion at the Sociology Department since the 70s. Together with Ion Aluaș, he edited the monumental anthology of contemporary French sociology (1971) and after 1990 he published numerous works in the field of mass communication.